2015
DOI: 10.2217/mmt.14.30
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PD1 and Anti-PD-L1 in the Treatment of Metastatic Melanoma

Abstract: Programmed cell death receptor-1 (PD-1) and programmed cell death-1 ligand-1 (PD-L1) represent promising novel targets in immunotherapy. PD-1 is an inhibitory receptor involved in T-cell regulation that is expressed by activated T cells. Nivolumab and pembrolizumab are anti-PD-1 antibodies that have shown antitumor activity and acceptable tolerability in patients with metastatic melanoma in preclinical development and Phase I/II clinical trials. Several ongoing Phase III studies are further investigating the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Monoclonal antibodies directed against the immune ­checkpoints – such as CTLA-4 (ipilimumab), PD-1 (nivolumab and pembrolizumab), or PD-L1 (BMS936559, MPDL3280A, and MEDI4736) – have been demonstrated to achieve durable antitumoral responses with significantly prolonged overall survivals in patients with metastatic melanoma ( 8 ). Despite the increased attention is currently paid to cancer immunotherapy (especially, treatments targeting PD-1/PD-L1 molecules) – which may become the standard of care in treating all unresectable stage III and IV melanomas, regardless of the BRAF mutational status, we here focused on molecular mechanisms involved in development and progression of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Monoclonal antibodies directed against the immune ­checkpoints – such as CTLA-4 (ipilimumab), PD-1 (nivolumab and pembrolizumab), or PD-L1 (BMS936559, MPDL3280A, and MEDI4736) – have been demonstrated to achieve durable antitumoral responses with significantly prolonged overall survivals in patients with metastatic melanoma ( 8 ). Despite the increased attention is currently paid to cancer immunotherapy (especially, treatments targeting PD-1/PD-L1 molecules) – which may become the standard of care in treating all unresectable stage III and IV melanomas, regardless of the BRAF mutational status, we here focused on molecular mechanisms involved in development and progression of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy is one important method for melanoma treatment, when alone or in combination with anti-PD-1 and anti-PD-L1 may improve survival rates ( Simeone, Grimaldi & Ascierto, 2015 ). Nivolumab is a PD-1 inhibitor with high affinity to PD-1 ( Hirano et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…It's typical clinical manifestations includes bloody diarrhea, abdominal pain, fecal urgency, and tenesmus, while anemia, fatigue and poor appetite as the concomitant symptom are also prevalent 2,3 . Autoimmune disease feaures the abnormalities of innate and adaptive immune responses, which also underlies the pathogenesis of UC 4–9 . Recent studies have shown that regimens to regulate the Th17/Treg cell balance could suppress autoimmune diseases pathogenesis and progression 7–9 .…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 Autoimmune disease feaures the abnormalities of innate and adaptive immune responses, which also underlies the pathogenesis of UC. 4 , 5 , 6 , 7 , 8 , 9 Recent studies have shown that regimens to regulate the Th17/Treg cell balance could suppress autoimmune diseases pathogenesis and progression. 7 , 8 , 9 Unbalanced intestinal immune homeostasis caused by excessive activation of T cells was one of the important characteristics of UC, which leads to the release of pro‐inflammatory mediators, the abnormal aggregation of immune cells and the destruction of intestinal mucosal tissue.…”
Section: Introductionmentioning
confidence: 99%